Regulation of Released Alkali from Gel Polymer Electrolyte in Quasi‐Solid State Zn–Air Battery. Issue 10 (15th January 2023) - Li, Haihan; Guo, Jiaming; Mao, Yanqi; Wang, Guanbo; Liu, Jinlan; Xu, Yuncun; Wu, Zhiwei; Mei, Zhiwei; Li, Wenqiong; He, Yun; Liang, Xiaoguang
Abstract: Gel polymer electrolyte (GPE) in quasi‐solid state Zn–air battery (QSZAB) will release alkali during cycling, resulting in gradual dehydration of GPE, corrosion of Zn electrode, Zn dendrites growth, and therefore inferior performance. Here, hollow Sn microspheres are prepared on Zn substrate by the technique of colloidal self‐assembly. The inner surfaces of hollow Sn microspheres are modified by 2‐hydroxypropyl‐β‐cyclodextrin (hollow Sn‐inner HPβCD) to regulate the released alkali at GPE|anode interface. The hollow Sn‐inner HPβCD can lessen the leakage of released alkali, make stored alkali diffuse back to GPE during the charging process, and mitigate the loss of soluble Zn(OH)4 2− to suppress Zn dendrites growth. Resultantly, GPE in QSZAB with hollow Sn‐inner HPβCD exhibits a high retention capacity for alkaline solution. The cell also exhibits a long cyclic lifespan of 127 h due to the effective regulation of released alkali, which outperforms QSZAB without hollow Sn‐inner HPβCD by 7.94 times. This work rivets the regulation of released alkali at GPE|anode interface, providing new insight to improve QSZABs' performance. Abstract : Hollow Sn microspheres with hydrophilic inner surfaces are prepared to regulate the released alkali from gel polymer electrolyte (GPE) in quasi‐solid state Zn–air battery (QSZAB) during cycling. This structure can lessen the leakage of released alkali, make stored alkali diffuse back to GPE, and mitigate the loss of soluble Zn(OH)4 2−, resulting in improved performance of QSZAB.